Measuring MBA Student Learning: Does distance make a difference? - Kretovics, Mark; McCambridge, Jim (International Review of Research in Open and Distributed Learning, 2002)
This article reports on an exploratory research effort in which the extent of MBA student learning on twelve specific competencies relevant to effective business performance was assessed. The article focuses on the extent to which differences in student learning outcomes may be influenced by one of three different types of instructional delivery: on-campus, distance, and executive MBA. It affirms the high quality of learning that can occur via distance education and proposes a strategy to conduct summative, program-level assessment. Specific findings include participants in all three groups self-reporting significantly higher scores on seven of twelve outcomes (e.g., goal setting, help, information gathering, leadership, quantitative, theory, and technology skills). It also notes that distance MBA students self reported significantly higher scores than on-campus students on the learning outcomes related to technology, quantitative, and theory skills, and higher scores on technology skills than the executive MBA group. Implications for further research are discussed.